Criteria for Division and Development of Reserves of Upland Deposits by Open-Underground Method - T., Tadjiyev Sh.; S., Kobilov O.; A., Kurolov A.; Ganiyevich, Mustafoyev Islombek (Research Parks Publishing LLC, 2022)
This article deals with the problems of open-underground mining of upland deposits.